Unravelling the Role of Epigenetic Modifications in Development and Reproduction of Angiosperms: A Critical Appraisal - Kumari, Priyanka; Khan, Sajid; Wani, Ishfaq Ahmad; Gupta, Renu; Verma, Susheel; Alam, Pravej; Alaklabi, Abdullah (Frontiers in Genetics, 2022)
Epigenetics are the heritable changes in gene expression patterns which occur without altering DNA sequence. These changes are reversible and do not change the sequence of the DNA but can alter the way in which the DNA sequences are read. Epigenetic modifications are induced by DNA methylation, histone modification, and RNA-mediated mechanisms which alter the gene expression, primarily at the transcriptional level. Such alterations do control genome activity through transcriptional silencing of transposable elements thereby contributing toward genome stability. Plants being sessile in nature are highly susceptible to the extremes of changing environmental conditions. This increases the likelihood of epigenetic modifications within the composite network of genes that affect the developmental changes of a plant species. Genetic and epigenetic reprogramming enhances the growth and development, imparts phenotypic plasticity, and also ensures flowering under stress conditions without changing the genotype for several generations. Epigenetic modifications hold an immense significance during the development of male and female gametophytes, fertilization, embryogenesis, fruit formation, and seed germination. In this review, we focus on the mechanism of epigenetic modifications and their dynamic role in maintaining the genomic integrity during plant development and reproduction.